2010
DOI: 10.1243/09544070jauto1549
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Biodiesel Fuel

Abstract: Biodiesel, the fatty acid alkyl esters derived from vegetable oils, animal fats, or waste cooking oils, is an alternative to diesel fuel. One of the major technical issues with the use of biodiesel is its susceptibility to oxidation. Oxidation of biodiesel is a complex process which involves a number of mechanisms producing an array of chemical components such as aldehydes, acids, ketones, and oligomeric compounds. These components in turn increase the viscosity and deposits in the fuel beyond acceptable level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…99,100 The oxidation rate and products formed from all these processes are temperature and light dependent as well as dependent on the original fatty acid profile. 101 As oxidation deterioration advances, the …”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…99,100 The oxidation rate and products formed from all these processes are temperature and light dependent as well as dependent on the original fatty acid profile. 101 As oxidation deterioration advances, the …”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…The increase in viscosity with increasing oxidation of a biodiesel sample has been reported in previous studies. 22 The increase in viscosity has been related to a high level of biodiesel oxidation due to the presence of oligomers of high polarity and molecular weight forming undesirable deposits.…”
Section: Kinematic Viscositymentioning
confidence: 99%
“…This can lead to solid deposits and the formation of contaminants including alcohols and acids, and these in turn can have a damaging effect on the engine of a vehicle. Research has shown that biodiesel is less stable than regular diesel due to an increased proportion of unsaturated molecules [23]. The stability of the biodiesel can be affected by many different parameters, including the composition, oxygen content and the presence of antioxidants.…”
Section: Oxidative Stabilitymentioning
confidence: 99%